The early modern imagination :|the historical drama of Bond, Churchill, Brenton and McLean - Erdurucan, Büşra. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2019., 2019)
This thesis, with particular focus on British historical drama set in early modern Britain, explores how the genre, through its emphasis on the Other, reflects the fictional nature of national identity. The selected plays, namely, Edward Bond‘s Bingo (1973), Caryl Churchill‘s Light Shining in Buckinghamshire (1976), Howard Brenton‘s Anne Boleyn (2010) and Linda McLean‘s Glory on Earth (2017) re-enact the prominent conflicts of early modern Britain. Although over forty years the main emphasis of the plays changes, the concern for reclaiming a voice for the Other remains. The idea that historical facts are open to interpretation makes it possible for the playwrights to create alternative pasts and this in return enables the playwrights to refer to national identity as a fictive construct. Though the genre‘s problematic relationship with the issue of truth can find its voice in the danger of reconnecting the reader / audience with the past, the genre maintains the attempt to provide a critical point of view concerning the issues of historiography and nation that are based on othering and binary oppositions. At the end, it is concluded that historical drama is to remain a popular genre that always evolves and seeks to present a nation free from power relations.
Keywords: English drama -- 20th century -- Criticism and interpretation.